2006
DOI: 10.1080/17453670610046271
|View full text |Cite
|
Sign up to set email alerts
|

Hemiarthroplasty in worst cases is better than internal fixation in best cases of displaced femoral neck fractures: A prospective study of 683 patients treated with hemiarthroplasty or internal fixation

Abstract: Background Studies have shown that the degree of initial displacement and also comminution of the femoral calcar, size of the head and varus angulation are prognostic of failure in displaced femoral neck fracture. We have applied these radiographic criteria in order to select patients who would benefit from internal fixation as opposed to primary hemiarthroplasty, and this prospective study was conducted in order to monitor the results of this strategy.Methods 683 displaced fractures of the femoral neck were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 24 publications
3
32
0
Order By: Relevance
“…Results of our multivariate Cox-regression analysis are in contrast to the vast majority of trails [8][9][10][11][16][17][18]26] . Several studies reported higher one year mortality rates for HA than IF [18,26,27] .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Results of our multivariate Cox-regression analysis are in contrast to the vast majority of trails [8][9][10][11][16][17][18]26] . Several studies reported higher one year mortality rates for HA than IF [18,26,27] .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, cognitive impairment which was demonstrated to be a risk factor for higher mortality in hip fracture patients [4,31] was ignored. Similarly, other RCTs [10,11,32] and non-randomised studies did not respect patients who were confused or had neurologic impairment [17,18] as well as patients incapable of independent walking or who were bed-ridden [9,10] . Subsequently, at least one third of hip fracture patients are disobeyed according to our study cohort.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations